How do you factor y= x^3-2x^2+x-2?
3 Answers
Explanation:
"factor the terms "color(blue)"by grouping"
=color(red)(x^2)(x-2)color(red)(+1)(x-2)
"take out the "color(blue)"common factor "(x-2)
=(x-2)(color(red)(x^2+1))
x^2+1" can be factored using "color(blue)"difference of squares"
a^2-b^2=(a-b)(a+b)
"with "a=x" and "b=ito(i=sqrt-1)
=(x-2)(x+i)(x-i)larrcolor(red)"in factored form"
Explanation:
or
and bringing the common factor
solving the equation for
solving the equation for
graph{x^3-2x^2+x-2 [-10, 10, -5, 5]}
Explanation:
We will use a factoring method called grouping. If we group the first and the third and the second and the fourth together, each grout has its own greatest common factor:
Now we see another CF between the two terms :